Investigating the Impact of Nature in Designing Cultural Environments for Children - Sadafi, Nasibeh; Azhdari, L. (International Journal of Engineering and Management Sciences, 2020)
There is a tendency to communicate with nature in human beings as a set of emotional experiences. This study investigates the impact of organic architecture in creating cultural spaces for children. The concepts of nature, naturalist architecture and children educational psychology, from the perspective of scholars and researchers in this area are investigated. The children’s perception of nature and their feelings were assessed and one hundred forty respondents among the instructors of cultural centres in different regions of Tehran have answered the questionnaires. To investigate the hypotheses, Univariate T - test and F - test were applied. The results showed that the stimulation of the natural environment has a positive and meaningful effect on curiosity, participation, and fantasy in children, while they show their impressions of nature indirectly. Therefore, designing applicable spaces according to children’s physics, using appropriate colours and furniture as well as more environmentally-related spaces, can have positive effects on social participation, intuitive and verbal skills of the children.